Local field potential recordings from the pedunculopontine nucleus in a Parkinsonian patient. - Androulidakis, A; Khan, S; Litvak, V; Pleydell-Pearce, C; Brown, P; Gill, S (2008)
The pedunculopontine nucleus has recently been introduced as a new therapeutic target for deep brain stimulation in patients suffering from Parkinson's disease, particularly those with severe gait and postural impairment. Stimulation at this site is typically delivered at low frequencies in contrast to the high frequency stimulation required for therapeutic benefit in the subthalamic nucleus. Therefore, we looked for and demonstrated evidence of low frequency synchronization of activity in the pedunculopontine nucleus of a patient with Parkinson's disease that increased after treatment with dopamine and which might be mimicked by local deep brain stimulation at low frequency.